Effect of Heat Treatment on Post Weld Railway Track - Abdullahi P. NUHU; Kabir O. YUSUF; Aliyu O. ABDULRAHMAN; Kehinde A. LASISI (FUDMA Journal of Engineering and Technology, 2025)
The structural integrity of railway tracks is critically influenced by welding processes and subsequent treatments. This study investigates the effects of various post-weld heat treatment methods; annealing, normalizing, and tempering on the mechanical and microstructural properties of welded high-carbon steel railway tracks. Flash butt welding was used to join rail segments, followed by standard post-weld heat treatment protocols (Annealing: 900 oC for 1 hour, Normalizing: 920 oC for 45mins, Tempering: 850oC for 1 hour). Mechanical testing included tensile, hardness, impact, and fatigue tests conducted according to BS standards, while microstructural analysis was performed using a scanning electron microscope. The results demonstrated that normalizing yielded the highest ultimate tensile strength (750 MPa) and fatigue life (1,000,000 cycles), making it the most effective method under cyclic loading conditions. Annealing, while reducing hardness and tensile strength, significantly enhanced toughness, making it suitable for applications requiring higher ductility. Tempering provided a balanced improvement in both strength and toughness. Microstructural evaluation revealed refined and more uniform grain structures in heat-treated samples compared to as-welded specimens. Post-weld heat treatment significantly enhances the performance of welded railway tracks. Normalizing stands out as the most beneficial treatment for strength and durability, while tempering offers a well-rounded mechanical profile. These findings can guide optimized heat treatment strategies to extend the service life and reliability of railway infrastructure.
Keywords: Heat treatment, annealing, tempering, normalizing and fatigue life.